The Influence of Management Accounting Systems, Decentralization, Budgets and Environmental Uncertainty on Manager Performance In the Pharmaceutical Industry in Surabaya - Hariyanti Hariyanti (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The research conducted by the author is a replication study of research conducted by Purba in 1998 with the same title, namely the influence of management accounting systems, decentralization, budgets and environmental uncertainty on manager performance, but with different objects. The research carried out by Purba took as an object an insurance company in the Surabaya municipal area, while the research that the author put forward in this thesis took as an object the pharmaceutical industry in Surabaya. The author wants to know how much difference there is when using different research objects. Several managers are needed by a relatively large organization or company to carry out some of the tasks of top managers. This is necessary because top managers cannot possibly carry out management and supervision of all company activities as a whole. Therefore, there will be a delegation of authority from top managers to middle level managers or lower level managers.